Association between Alpha- Klotho Protein, Calcium, and Phosphate concentrations in Adult Iraqi Patients with Beta-Thalassemia Major - Ahmed J. Kadhim; Hedef D. El-Yaseen; Ali M. Jawad (مجلة كلية الطب)
Background: Beta-thalassemia major is a prevalent global condition characterized by a rapid breakdown of red blood cells. Regular blood transfusions can give rise to problems such as cardiovascular disease, diabetes, osteoporosis, and renal disorders. Alpha-Klotho protein is a protein that has anti-aging properties and is involved in several functions, including reducing oxidative stress, regulating energy metabolism through several routes, and managing calcium and phosphate metabolism.